Marketing of New Party-Political Towards the 2024 Election Winning Strategy of the Indonesian People's Wave Party - Danan Setiawan; I Made Sukresna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The general election in the State of Indonesia is held before the term of office of the previous official runs out, which is 5 years. Every 5 years the people of Indonesia will hold elections to choose their leader. In 2019, Indonesia held simultaneous elections, namely legislative elections and presidential-vice presidential elections, but there were several new polemics that occurred at that time, namely Law No. 7 of 2017 which states that the pair of presidential and vice-presidential candidates must be supported by at least 20% of dpr officials or 25% of the votes of the entire Indonesian people. This is set as a condition to determine whether or not the candidates for the presidential and vice-presidential candidates in the general election. In addition, there are regulations regarding the threshold of minimum party votes or Parliamentary Threshold of 4% of the vote for political parties can occupy the seat of the House of Representatives. So, this research is more likely to discuss how new political parties in Indonesia such as the Indonesian Gelora Party in conducting political manufer to be able to pass the parliamentary threshold in the 2024 election.  The purpose of this study is to observe what the Indonesian Gelora Party has done and will do in order to pass the parliamentary threshold and win the 2024 legislative elections, and apply the concept of political marketing in order to win the Indonesian Gelora Party in the 2024 general election, by getting votes above the parliamentary threshold.  This research uses qualitative methods with a case study approach. Techniques in collecting data are observation and in-depth interviews. The results of the research obtained show that the Indonesian Gelora Party as a new party has conducted massive political marketing by offering its platform as a political product in the form of a big narrative of the Indonesian nation towards the world's top five.  Public appreciation of the consistency attitude of the Indonesian Gelora Party is seen from when Gelora faced the reality of plurality of religious relations with the State, relations between tribes, ethnicities that smell of politics, relations between groups with diverse forces and with the State.